US–Canada Beaufort Sea Maritime Boundary Dispute in the Perspective of International Law - I. V. Bunik (Московский журнал международного права, 2018)
Introduction. Maritime boundary disputes and exercising sovereignty in the Arctic are of great current interest in the International Law since there is no uniform understanding of the limits of applicability of the United Nations Convention on the Law of the Sea 1982 to the Arctic Ocean taking into account the international customary law and historic rights of the coastal states. One of such disputes is the US-Canada Beaufort Sea maritime boundary dispute which is of vast importance due to the hydrocarbon exploration of these states in the outlined area as well as due to the conclusion and entry into force of the Treaty between the Kingdom of Norway and the Russian Federation concerning Maritime Delimitation and Cooperation in the Barents Sea and the Arctic Ocean 2010.Materials and methods. The theoretical background of this research consists of works of distinguished Russian and foreign scholars and specialists in International Law. The analytical framework includes the treaties between Arctic coastal states concerning maritime delimitation (the Convention Concerning the Limits of Their Respective Possessions on the Northwest Coast of America and the Navigation of the Pacific Ocean 1825, Treaty concerning the Cession of the Russian Possessions in North America by his Majesty the Emperor of all the Russia to the United States of America 1867, Agreement between the United States of America and the Union of Soviet Socialist Republics on the maritime boundary 1990), national legislation of the US and Canada, diplomatic notes. The research is based on methods such as formal logic, including analysis, synthesis, analogy and modeling historical research, as well as systematic, historical and comparative methods.Research results. Based on the results of the study, the author notes that there are considerable differences in the US and Canada’s legal stances concerning the disputed area of the Beaufort Sea, including in particular the opposing views of these states on the applicability of the Convention 1825 to their relations (according to Canada, it applies to maritime areas, whereas the US favours its literal construction which limits its scope to land areas).  The US and Canada also base their claims on the rules on special circumstances and the doctrine of estoppel which are reflected in their national legislation. The legal analysis of the different approaches to the resolution of the dispute in question allows making the conclusion on the perspective and necessity of its settlement, particularly, in the context of the Russian Arctic claims.Discussion and conclusions. Based on the legal analysis of the international treaties on the Arctic delimitation, US and Canada national legislation and doctrinal views, the author comes to the conclusion that sustaining the status-quo is beneficial for both parties since it does not affect the legal positions of other states in similar disputes, nor does it hinder the international cooperation in the Arctic.